Banking and credit in the framework of new economic policies in Eastern Europe - GARVY, G. (PSL Quarterly Review, 2014)
<!–[if gte mso 9]> 72 1024x768 <![endif]–> In recent times all of the countries of Eastern Europe, save Roumania, have proclaimed their intention to undertake significant changes in their economies. The reforms announced or already initiated amount to a considerable departure from the centrally planned command economies that emerged with the establishment of communist regimes after World War II. The present study focuses on those common features of the new economic policies which affect the future role of money, credit and banking in Eastern Europe. The author first outlines the underlying factors that have motivated the changes before considering the economic system in which they are to be placed. The trend toward greater flexibility in the area of banking and credit is then analysed. Finally, the emerging use of credit as an “economic lever” is considered. JEL: G21, E51 <!–[if gte mso 9]> Normal 0 14 <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>